Balancing the right of gig economy workers in the context of collective bargaining - Amin, Noor Shuhadawati (IIUM Press, 2023)
Collective bargaining forms an integral part of a trade union. In Malaysia, workers are protected under the relevant employment legislations that provide basic minimum rights. Although Malaysia’s freedom of association is embodied in the Federal Constitution, the rights of the gig economy workers, more often than not, are neglected. This is evident from the exclusion of this category of workers from the definition stated in the employment legislations. With this exclusion, gig economy workers are denied from establishing and joining a trade union. This subsequently unable them to have collective bargaining powers that resulted in the exploitation of their rights. The method adopted in this study is doctrinal in nature by analysing various employment related legislations and international conventions relating to trade union and collective bargaining and decided cases. It has been revealed that the weak definition of workmen impedes the right of workers in the gig economy to form a trade union. Based on the shortcoming identified, it is understood that the government plays a critical role in helping these workers to overcome barriers through strengthening the available legislations. This study proposed for gig economy workers to utilise other avenues currently available in other countries with the hope that collective agreement, non-binding agreement and application-based society exclusively for gig economy workers that could eventually lead to the forming of a trade union.